Towards uncertainty quantification of the ONERA 7A rotor using comprehensive analysis - Salah El Din, I.; Khurana, M.; Yeo, H. (My University, 2021)
The uncertainty and sensitivity of rotor blade torsion stiffness on rotor power and maximum torsion moment is studied. Comprehensive analysis tools are used to establish rotor performance and structural loads. A global-based uncertainty propagation scheme was applied using a scaling factor to uniformly induce spanwise variability in blade torsion stiffness using Monte Carlo simulations. A local-based uncertainty propagation scheme was also applied with a third-order polynomial function to induce a non-uniform distribution of material stiffness. The analysis confirmed that uncertainty in torsion stiffness has negligible impact on rotor power and maximum amplitude torsion moment along the blade span for the considered high-speed case. The analysis does confirm a pronounced effect on half peak-to-peak torsion moment at specific blade span stations where experimental measurements are available. Additionally, a sensitivity analysis using a non-uniform distribution approach with a scaling factor facilitated a comprehensive quantification of the direct and interaction effects between the uncertain parameters on the response outputs.